2023
DOI: 10.3390/jcm12144865
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Rehabilitation after Anterior Cruciate Ligament Reconstruction through Telerehabilitation with Artificial Intelligence Brace during COVID-19 Pandemic

Abstract: Background: Due to the rapid spread of the coronavirus disease-19 (COVID-19), most of the patients expressed a reluctance to undergo postoperative rehabilitation at a rehabilitation clinic. Therefore, in this scenario it was necessary to reshape the crucial role of postoperative rehabilitation of these patients. We conducted a telerehabilitation program based on an artificial intelligence brace (AI brace) which can monitor the progress of rehabilitation through an app and an internet server. Our hypothesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The inaccessibility of face-to-face post-operative rehabilitation during this period has prompted the swift emergence of contactless rehabilitation methods [ 28 ].Supervised rehabilitation under the guidance of a licensed therapist might prove more efficacious than engaging in unsupervised exercise [ 29 ]. A retrospective cohort study found that telerehabilitation after ACLR seems to provide a superior short-term outcome compared to hospital-based rehabilitation during the COVID-19 pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inaccessibility of face-to-face post-operative rehabilitation during this period has prompted the swift emergence of contactless rehabilitation methods [ 28 ].Supervised rehabilitation under the guidance of a licensed therapist might prove more efficacious than engaging in unsupervised exercise [ 29 ]. A retrospective cohort study found that telerehabilitation after ACLR seems to provide a superior short-term outcome compared to hospital-based rehabilitation during the COVID-19 pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the impossibility of in-person rehabilitation during the COVID-19 pandemic, a telerehabilitation program utilizing an AI brace was implemented for patients undergoing ACLR. The tele-AI patients, receiving remote rehabilitation, demonstrated superior short-term outcomes with higher International Knee Documentation Committee scores (IKDC) and Knee Injury and Osteoarthritis Outcome Scores (KOOS) at various intervals compared to the face-to-face patients undergoing hospital-based rehabilitation [94]. Notably, the tele-AI group exhibited a higher Tegner Activity Scale (TAS) after one year.…”
Section: Rehabilitationmentioning
confidence: 99%
“…9 In recent years, several approaches have been using communication technologies to deliver rehabilitation services to individuals at their homes following ACLR. 10 While some evidence suggests that these approaches may be equally beneficial as conventional CR, the available data are insufficient to support their effectiveness in patient-and clinician-reported outcomes fully. 11 Internet-based interventions can potentially improve postoperative recovery by ensuring treatment continuity and providing patients with real-time feedback.…”
Section: What This Study Addsmentioning
confidence: 99%